Fluorinated nanoparticle, composite material, preparation method of fluorinated nanoparticle and composite material, and application of fluorinated nanoparticle and composite material

By coupling fluorinated groups with specific modification ratios on the surface of nanoparticles, fluorinated nanoparticles with hydrophilicity and fluorophilicity are prepared, which solves the problem of poor dispersion of drug-loaded nanoparticles in fluorine-phase liquids and improves the drug Load efficiency and droplet stability provide new solutions for drug delivery.

CN119424674APending Publication Date: 2025-02-14PEKING UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410381102.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-01
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently disperse drug-loaded nanoparticles in fluorine phase liquids, resulting in a decrease in drug load efficiency and a decrease in shell stability.

Method used

By coupling a specific modified ratio of fluorinated groups on the surface of the nanoparticles, fluorinated nanoparticles with hydrophilicity and fluorophilicity can be prepared, so that they can be efficiently dispersed and stably embedded in the droplets of the fluorine-containing liquid.

Benefits of technology

It improves the load efficiency of drugs and the stability of droplets, promotes the development of droplets in scientific research and clinical fields, and provides an effective solution for drug delivery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119424674A_ABST
    Figure CN119424674A_ABST
Patent Text Reader

Abstract

The invention relates to the field of biological medicine, and provides a fluorinated nanoparticle, a composite material and a preparation method and application of the fluorinated nanoparticle and the composite material, and the fluorinated nanoparticle comprises a nanoparticle and a fluorinated group which is connected with the nanoparticle through an amido bond and is located on the outer layer of the nanoparticle; in the fluorinated nanoparticles, the amino substitution rate is 35%-65%. According to the fluorinated nanoparticles, the drug-loaded nanoparticles can be efficiently dispersed and stably embedded into the liquid drops of the fluorine-containing phase liquid, so that the loading efficiency of the drug and the stability of the liquid drops are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedicine, and in particular to a fluorinated nanoparticle, application of the fluorinated nanoparticle in preparing a hydrophilic and fluorinated carrier, a composite material, a method for preparing the composite material, and application of the fluorinated nanoparticle or the composite material in drug delivery. Background Art

[0002] As a drug carrier, droplets have many advantages. Due to their large volume, they can carry a variety of drugs and drug carriers, encapsulate drug-loaded nanoparticles, fluorescent molecules, gene drugs and chemical drugs, etc.; they can also be combined with ultrasonic blasting technology to achieve targeted drug release; and they have high blood circulation stability and high biocompatibility. In addition, their core is usually a perfluorocarbon liquid, so they have good droplet formation performance and stability.

[0003] However, due to the hydrophilic or lipophilic properties of drug-loaded nanoparticles, the particles are difficult to effectively disperse in the fluorine phase liquid. Current methods can usually only load drug-loaded nanoparticles in the shell layer of droplets, resulting in reduced drug loading efficiency and decreased shell stability.

[0004] Therefore, it is necessary to develop drug-loaded nanoparticles that can be efficiently dispersed in fluorine-phase liquids so that the drug-loaded nanoparticles can be stably embedded in the droplets, thereby improving the drug loading efficiency and stability of the droplets. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and provide a fluorinated nanoparticle. The present invention also provides the use of the fluorinated nanoparticle in the preparation of a hydrophilic and fluorine-friendly carrier, a composite material, a method for preparing the composite material, and the use of the fluorinated nanoparticle or the composite material in drug delivery, so as to achieve efficient dispersion and stable embedding of the nanoparticles in the droplets of the fluorine-containing phase liquid, thereby improving the drug loading efficiency and the stability of the droplets.

[0006] In order to achieve the above object, the first aspect of the present invention provides a fluorinated nanoparticle, wherein the fluorinated nanoparticle comprises a nanoparticle and a fluorinated group connected to the nanoparticle through an amide bond and located on the outer layer of the nanoparticle; In the fluorinated nanoparticles, the amino substitution rate is 35%-65%.

[0007] Preferably, the fluorinated group comprises one or more of the groups represented by Formula I and Formula II; Formula I; Formula II; Wherein, * indicates connecting amide bonds; In Formula I, x is an integer of 0-3, y is an integer of 0-20, and z is an integer of 0-8; when y is 0, R1 is CF3, CHF2 or CH2F, and when y is not 0, R1 is CH3, CF3, CHF2 or CH2F; In formula II, R2 to R6 are each independently H, CH3, OH, NO2O, CF3, F, CH2OH, CN, NCO or (CF2) a CF3, and at least one of R2 to R6 is a F-containing group; a is an integer of 1-20.

[0008] Preferably, the fluorinated nanoparticles contain a drug.

[0009] More preferably, in the fluorinated nanoparticles, the weight ratio of the drug to the nanoparticles is 0.05-50:1.

[0010] The second aspect of the present invention provides a method for preparing the fluorinated nanoparticles described in the first aspect, the method comprising: under reaction conditions, by chemical coupling method, coupling the fluorinating agent with the nanoparticles through amide bonds to obtain fluorinated nanoparticles.

[0011] The third aspect of the present invention provides the use of the fluorinated nanoparticles described in the first aspect in the preparation of a hydrophilic and fluorine-free carrier.

[0012] The fourth aspect of the present invention provides a composite material, comprising a biocompatible shell layer and a fluorine-phase liquid encapsulated in the shell layer, wherein the fluorinated nanoparticles described in the first aspect are dispersed in the fluorine-phase liquid.

[0013] The fifth aspect of the present invention provides a method for preparing the composite material according to the fourth aspect, the method comprising: (1) mixing fluorinated nanoparticles and fluorine phase liquid to obtain material A; (2) mixing the biocompatible material with the hydration liquid to obtain material B; (3) Mixing material A and material B and performing emulsification treatment to obtain the composite material.

[0014] Preferably, the emulsification treatment is carried out by one or more of mechanical oscillation, ultrasonic cavitation and homogenization.

[0015] Preferably, the conditions for ultrasonic cavitation include: ultrasonic power of 60W-200W, ultrasonic time of 0.1min-10min, and duty cycle of 20%-60%.

[0016] The sixth aspect of the present invention provides use of the fluorinated nanoparticles described in the first aspect or the composite material described in the fourth aspect in drug delivery.

[0017] The present invention adopts the above technical solution to achieve the following beneficial effects: (1) The present invention innovatively uses fluorinated nanoparticles with fluorinated groups of a specific modification ratio coupled to the surface of the nanoparticles, so that the fluorinated nanoparticles have both hydrophilicity and fluorine affinity, and achieve efficient dispersion and stable embedding of nanoparticles in the droplets of fluorine-containing phase liquid, thereby improving the drug loading efficiency and droplet stability, and promoting the development of droplets in scientific research and clinical fields. Therefore, this fluorinated drug-loaded nanoparticle has a wide range of application prospects and can be applied to the fields of drug delivery, cancer treatment, and disease diagnosis, providing an effective solution for drug delivery. Combined with ultrasonic spot blasting technology, it can open up new possibilities for personalized medicine and precision treatment.

[0018] Under preferred conditions, further combining the ratio of nanomaterials and drugs and specific preparation methods based on the modification ratio of fluorinated groups can further obtain fluorinated drug-loaded nanoparticles with more uniform particle size within 500 nm, and can achieve a higher encapsulation rate.

[0019] (2) During the preparation process, the fluorinated nanoparticles described in the present invention are combined with preferred droplet shell components (including lipids, emulsifiers and surface charge modifiers) and ratios, preferred hydration liquids and preferred ultrasonic parameters to prepare droplets with higher uniformity and a particle size between 500-1000nm, ultimately obtaining a double-layer encapsulated drug cascade delivery carrier with efficient drug loading and ultrasonic response.

[0020] (3) The composite material provided by the present invention is used as a double-layer wrapped drug cascade delivery carrier. After intravenous injection into the body, the outer layer of droplets can explode at the targeted site under the action of ultrasound, releasing nanoparticles, and achieving precise delivery of drugs into cells, better meeting the needs of different types of drugs for delivery carriers in clinical and scientific research, and providing new solutions for the field of drug delivery and treatment.

[0021] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The figure shows an optical microscope image of the composite material prepared in Example 1 under 40 times objective lens labeled with cy3.

[0023] Figure 2Shown are ultrasonic images of the composite material prepared in Example 1 before and after in vitro ultrasonic activation. DETAILED DESCRIPTION

[0024] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0025] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0026] The first aspect of the present invention provides a fluorinated nanoparticle, the fluorinated nanoparticle comprising a nanoparticle and a fluorinated group connected to the nanoparticle via an amide bond and located on the outer layer of the nanoparticle; In the fluorinated nanoparticles, the amine substitution rate is 35%-65%, for example, 35%, 40%, 45%, 50%, 55%, 60% or 65%.

[0027] In the present invention, the amine substitution rate is the ratio of amine groups (amide bonds) substituted by fluorinated groups to the total amine groups in the nanoparticles, that is, the ratio of fluorinated groups to the sum of fluorinated groups and amine groups (that is, the part not substituted by fluorinated groups).

[0028] In some embodiments, the fluorinated group comprises one or more of the groups represented by Formula I and Formula II: Formula I; Formula II; Wherein, * indicates connecting amide bonds; In Formula I, x is an integer of 0-3, y is an integer of 0-20, and z is an integer of 0-8; when y is 0, R1 is CF3, CHF2 or CH2F, and when y is not 0, R1 is CH3, CF3, CHF2 or CH2F; In formula II, R2 to R6 are each independently H, CH3, OH, NO2O, CF3, F, CH2OH, CN, NCO or (CF2) a CF3, and at least one of R2 to R6 is a F-containing group; a is an integer of 1-20.

[0029] In some embodiments, in Formula I, x is an integer from 0 to 1, y is an integer from 0 to 15, and z is an integer from 0 to 2.

[0030] In some embodiments, the group shown in Formula I is selected from one or more of C1-C15 perfluoroalkyl groups (such as perfluoromethyl, perfluoroethyl, perfluoropropyl, perfluorobutyl, perfluoropentyl, perfluorohexyl, perfluoroheptyl, perfluorooctyl, perfluorononyl, perfluorodecyl, perfluoroundecyl, perfluorododecyl, perfluorotridecyl, perfluorotetradecyl or perfluoropentadecyl) and derivatives thereof.

[0031] In some embodiments, in Formula II, R2 to R6 are each independently H, F, CF3 or (CF2) a CF3.

[0032] In some embodiments, in Formula II, a is an integer of 1-10 (eg, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10).

[0033] In some embodiments, the group represented by Formula II is selected from one or more of 3-fluorobenzyl, 3,5-difluorobenzyl, 2,3,5,6-tetrafluoro-4-methylbenzyl, pentafluorobenzyl, 2-fluoro-3-(trifluoromethyl)benzyl and derivatives thereof.

[0034] In some embodiments, the average particle size Dv of the fluorinated nanoparticles is 50 10 nm - 800 nm, for example, 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm or 800 nm.

[0035] In some embodiments, the average particle size Dv of the fluorinated nanoparticles is 50 It is 50nm-500nm.

[0036] In some embodiments, the polydispersity coefficient of the fluorinated nanoparticles is 0.02-0.03.

[0037] In some embodiments, the nanoparticles are lipid nanoparticles or polymer nanoparticles.

[0038] In some embodiments, the lipid nanoparticles contain ionizable cationic lipids, cholesterol (CHO), auxiliary phospholipids and pegylated lipids. The cationic lipid portion of the lipid nanoparticles undergoes an amidation reaction with a carboxyl group or anhydride in a fluorinating agent via a primary amino group, thereby obtaining the fluorinated nanoparticles.

[0039] In some embodiments, the ionizable cationic lipid is selected from one or more of DOTAP-Cl, DC-CHOL, DLin-MC3-DMA, SM-102, and ALC-0315.

[0040] In some embodiments, the auxiliary phospholipid is selected from one or more of 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC), dioleoylphosphatidylethanolamine (DOPE), and dipalmitoylphosphatidylcholine (DPPC).

[0041] In some embodiments, the PEGylated lipid is selected from one or more of ALC-0159, PEG2000-DMG, mPEG2000-DMG, and DSPE-MPEG2000.

[0042] In some embodiments, in the lipid nanoparticles, the molar ratio of ionizable cationic lipid, cholesterol, auxiliary phospholipid and polyethylene glycol is (20-60, such as 20, 25, 30, 35, 40, 45, 50, 55 or 60): (30-50, such as 30, 35, 40, 45 or 50): (5-60, such as 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55 or 60): (1-30, such as 1, 5, 10, 15, 20, 25 or 30).

[0043] In some embodiments, the polymer nanoparticles are selected from one or more of linear polymers, dendrimer polymers, and hyperbranched polymers.

[0044] In some embodiments, the raw material of the polymer nanoparticles is a polymer modified with a primary amino group, and the polymer undergoes an amidation reaction with a carboxyl group or anhydride in a fluorinating agent via the primary amino group, thereby obtaining the fluorinated nanoparticles.

[0045] In some embodiments, the polymer is selected from one or more of polysaccharides (such as chitosan, cyclodextrin, sodium alginate, dextran) and their derivatives, aliphatic polyester polymers (such as polylactic acid (PLA), polyglycolide (PLG), polyglycolide-lactide copolymer (PLGA)), polyglutamic acid (g-PGA), polyethylene glycol (PEG), polystyrene and polyamide (such as polyamidoamine type (PAMAM) dendrimer).

[0046] In some embodiments, the fluorinated nanoparticles comprise a drug.

[0047] In some embodiments, the drug is a chemotherapeutic drug and / or a nucleic acid drug.

[0048] In some embodiments, the chemotherapy drug is one or more of Carboplatin, Oxaliplatin, Tegafur, Methotrexate, Fluorouracil, Cisplatin, Capecitabine, Paclitaxel, Docetaxel, Dexamethasone, Actinomycin D, Etoposide, and Doxorubicin.

[0049] In some embodiments, the nucleic acid drug is one or more of small interfering RNA (siRNA), small RNA (shRNA), antisense strand or antisense oligonucleotide (ASO) of deoxyribonucleic acid (DNA) or ribonucleic acid (RNA) sequence, non-coding RNA molecules that regulate gene expression, CRISPR-Cas9 system, zinc finger nucleases, and mRNA and DNA vaccines.

[0050] In some embodiments, in the fluorinated nanoparticles, the weight ratio of the drug to the nanoparticles is 0.05-50:1, for example, 0.05:1, 0.1:1, 0.5:1, 1:1, 5:1, 10:1, 15:1, 20:1, 39:1, 40:1 or 50:1.

[0051] The second aspect of the present invention provides a method for preparing the fluorinated nanoparticles described in the first aspect, the method comprising: under reaction conditions, by chemical coupling method, coupling the fluorinating agent with the nanoparticles through amide bonds to obtain fluorinated nanoparticles.

[0052] In some embodiments, the fluorinating agent comprises one or more of the fluorinated groups shown in Formula I and Formula II.

[0053] In some embodiments, the fluorinating agent is one or more of carboxylic acid compounds and their derivatives and anhydride compounds and their derivatives.

[0054] In some embodiments, when the fluorinating agent comprises a fluorinated group as shown in Formula I, the fluorinating agent includes but is not limited to trifluoroacetic acid, pentafluoropropionic acid, heptafluorobutyric acid, nonafluoropentanoic acid, undecafluorohexanoic acid, tridecafluoroheptanoic acid, pentafluorooctanoic acid, heptadecafluorononanoic acid, nonadecafluorodecanoic acid, perfluorobutyric anhydride, perfluoroheptanoic anhydride, perfluorodecanoic anhydride, 2,2,3,3,4,4,4-heptafluorobutyl acrylate, 3-(1H,1H,5Hoctafluoropentyloxy)-1,2-epoxypropylene, nonafluorobutylsulfonamide anhydride, perfluoroacetic acid (TFA, CF3COOH), perfluoropropionic acid (PFPrA, C2F5COOH), perfluorobutyric acid (PFBA, C3F7COOH), perfluoropentanoic acid (PFPA, C4F9COOH), perfluorohexanoic acid (PFHxA, C5F 11 COOH), perfluoroheptanoic acid (PFHpA, C6F 13 COOH), perfluorooctanoic acid (PFOA, C7F 15 COOH), perfluorononanoic acid (PFNA, C8F 17 COOH), perfluorodecanoic acid (PFDA, C9F 19 COOH), perfluoroundecanoic acid (PFUDA, C 10 F 21 COOH), perfluorododecanoic acid (PFDoDA, C 11 F 23 COOH), perfluorotridecanoic acid (PFTrDA, C 12 F 25 COOH), perfluorotetradecanoic acid (PFTeDA, C 13 F 27 COOH) and its derivatives.

[0055] In some embodiments, when the fluorinating agent comprises a fluorinated group as shown in Formula II, the fluorinating agent includes but is not limited to one or more of 3-fluorobenzoic acid, 3,5-difluorobenzoic acid, 2,3,5,6-tetrafluoro-4-methylbenzoic acid, pentafluorobenzoic acid, 2-fluoro-3-(trifluoromethyl)benzoic acid and derivatives thereof.

[0056] In some embodiments, the chemical coupling method is a carboxyl-amino reaction coupling method.

[0057] In some embodiments, the chemical coupling method comprises: (a) adding a fluorinating agent, 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysulfosuccinimide (Sulfo-NHS) to an activation buffer in sequence, and then reacting for 5 min to 30 min; (b) adding a first quenching agent (such as 2-mercaptoethanol) to the reaction product of step (a) to quench the reaction, and then adjusting the pH of the reaction system to 7-9 to obtain solution ①; (c) mixing the nanoparticles with water and adjusting the pH to 7-9 to obtain solution ②; (d) adding solution ② to solution ①, mixing and reacting for 0.5 h to 24 h, and then adding a second quenching agent (such as hydroxylamine hydrochloride) to quench the reaction; (e) purifying the product obtained in step (d) to obtain a fluorinated nanomaterial.

[0058] In step (a), the fluorinating agent and EDC may be added first and reacted for 5-15 minutes before adding Sulfo-NHS.

[0059] In some embodiments, the molar ratio of the fluorinating agent, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysulfosuccinimide is (1-40, such as 1, 5, 10, 15, 20, 25, 30, 35, 40): (2-50, such as 2, 5, 10, 15, 20, 25, 30, 35, 40, 45 or 50): (2-50, such as 2, 5, 10, 15, 20, 25, 30, 35, 40, 45 or 50).

[0060] In some embodiments, the activation buffer comprises morpholineethanesulfonic acid (MES) and NaCl.

[0061] In some embodiments, in the activation buffer, the molar ratio of morpholineethanesulfonic acid to NaCl is (1-20, such as 1, 5, 10, 15 or 20): (1-30, such as 1, 5, 10, 15, 20, 25 or 30).

[0062] In step (a), there is no particular limitation on the amount of the activation buffer, as long as it can dissolve the substance added thereto. In some embodiments, compared to 1 g of the fluorinating agent, the amount of the activation buffer is 0.5 mL-50 mL, for example, 0.5 mL, 1 mL, 5 mL, 10 mL, 20 mL, 30 mL, 40 mL or 50 mL.

[0063] In steps (b) and (c), PBS buffer or other non-amine buffer may be used to adjust the pH, and the PBS buffer may be obtained, for example, from Thermo Scientific™ product No. 28372. In some embodiments, the PBS buffer comprises 0.5M-1.5M sodium phosphate, 0.075-0.225M NaCl, pH 7.2-7.5.

[0064] In some embodiments, in step (d), the reaction temperature is 0-40°C, such as 0°C, 4°C, 10°C, 20°C, 30°C or 40°C.

[0065] In some embodiments, in step (d), the reaction temperature is 3-30°C.

[0066] In the present invention, unless otherwise specified, the reaction condition is room temperature (eg, 10-40° C.).

[0067] In the present invention, the water used may be DEPC water, that is, ultrapure water (primary water) treated with DEPC (diethyl pyrocarbonate) and sterilized at high temperature and high pressure, and does not contain impurities such as RNA, DNA and protein.

[0068] In the present invention, the amount of the quencher is excessive. In some embodiments, the amount of the first quencher added is such that the final concentration of the first quencher in the reaction system is 1 mM-10 mM. In some embodiments, the amount of the second quencher added is such that the final concentration of the second quencher in the reaction system is 1 mM-20 mM.

[0069] In step (e), purification can be carried out in a conventional manner in the art, for example, dialysis can be performed to remove NHS and EDC-NHS using a dialysis tube (the time can be 10 min-60 min), followed by washing with DEPC water and freeze-drying to obtain the fluorinated nanomaterial.

[0070] When the fluorinated nanoparticles are loaded with drugs, the drug loading method may be a conventional method in the art, such as mixing the drug and the fluorinated nanoparticles by one or more of a self-assembly method or a thin film emulsification method to obtain fluorinated drug-loaded nanoparticles.

[0071] In some embodiments, the self-assembly method comprises mixing the drug and the fluorinated nanoparticles in water. The mixing conditions may include a pH of 1-10, such as 1, 3, 5, 7, 9 or 10, and a temperature of 1°C-50°C, such as 1°C, 5°C, 10°C, 20°C, 30°C, 40°C or 50°C.

[0072] In some embodiments, the thin film emulsification method includes mixing the drug and fluorinated nanoparticles in an organic solvent and rotary evaporating for 10 min -60 min at a pH of 1-10 (e.g., 1, 3, 5, 7, 9 or 10), a temperature of 2°C-99°C (e.g., 2°C, 10°C, 20°C, 40°C, 60°C, 80°C or 90°C), and a vacuum degree of 0.01 MPa -0.1 MPa (e.g., 0.01 MPa, 0.02 MPa, 0.04 MPa, 0.06 MPa, 0.08 MPa or 0.1 MPa), followed by adding water for emulsification, and then rotating at 1°C-50°C for 10 min -120 min.

[0073] The drug-loaded material can be used for the subsequent preparation of composite materials, or can be freeze-dried to obtain freeze-dried powder and then used for the preparation of composite materials.

[0074] The third aspect of the present invention provides the use of the fluorinated nanoparticles described in the first aspect in the preparation of a hydrophilic and fluorine-free carrier.

[0075] The fourth aspect of the present invention provides a composite material, comprising a biocompatible shell layer and a fluorine-phase liquid encapsulated in the shell layer, wherein the fluorinated nanoparticles described in the first aspect are dispersed in the fluorine-phase liquid.

[0076] In some embodiments, the particle size of the composite material is 5-50 times, such as 5 times, 8 times, 10 times, 15 times, 20 times, 30 times, 40 times, or 50 times, the particle size of the fluorinated nanoparticles.

[0077] In some embodiments, the average particle size Dv of the composite material is 50 It is 500nm-1000nm, for example, 500nm, 600nm, 700nm, 800nm, 900nm or 1000nm.

[0078] In some embodiments, the composite material has a polydispersity coefficient of 0.1-0.3.

[0079] In some embodiments, the biocompatible shell comprises a lipid.

[0080] In some embodiments, the lipid is a phospholipid. A phospholipid comprises a polar head group and a non-polar group.

[0081] In some embodiments, the polar head group of the phospholipid is PC (acylcholine), PE (acylethanolamine), PG (sodium acylglycerate), PS (acylserine) and PA (glycerophosphatidic acid); the non-polar group is a long carbon chain with a length of 16-28, which can be selected from 1,2-distearoyl-sn-glyceryl-3-phosphocholine (DSPC), distearoylphosphatidylethanolamine (DSPE), dipalmitoylphosphatidylcholine (DPPC), dioleoylphosphatidylcholine (DOPC), diarachidonylphosphatidylcholine (DAPC), One or more of 1,2-bis(diphenylphosphino)ethane (DPPE), dioleoylphosphatidylethanolamine (DOPE), distearoylphosphatidylglycerol (DSPG), dipalmitoylphosphatidylglycerol (DPPG), dimyristoylphosphatidylglycerol (DMPG), distearoylphosphatidic acid (DSPA), dipalmitoylphosphatidic acid (DPPA), dipalmitoylphosphatidylserine (DPPS), distearoylphosphatidylserine (DSPS) and distearoylphosphatidylethanolamine-polyethylene glycol (DSPE-PEG).

[0082] In some embodiments, the composite material further comprises an emulsifier and optionally cholesterol.

[0083] In some embodiments, the emulsifier is selected from one or more of polyethylene glycol 4000, polyethylene glycol 40s, polyoxypropylene polyoxyethylene block polyether, polyethylene glycol 1400 and polysorbate 80.

[0084] In some embodiments, relative to 100 parts by weight of lipid, the emulsifier content is 10-80 parts by weight, such as 10 parts by weight, 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight, 70 parts by weight or 80 parts by weight, and the cholesterol content is less than 60 parts by weight, such as 0 parts by weight, 10 parts by weight, 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight or 60 parts by weight.

[0085] In some embodiments, the emulsifier is present in an amount of 10-60 parts by weight relative to 100 parts by weight of the lipid.

[0086] In some embodiments, the cholesterol content is 10-60 parts by weight relative to 100 parts by weight of the lipid.

[0087] In some embodiments, the fluorine-phase liquid is an organic fluorine that can phase-change liquid, that is, "phase-change liquid" means that it can be liquid under normal temperature and pressure conditions or under certain environmental conditions at room temperature, but can be transformed into gas at room temperature under specific environmental or excitation conditions.

[0088] In some embodiments, the fluorine phase liquid is a perfluorocarbon, preferably selected from perfluorocarbons above C3, such as one or more selected from perfluoropropane, perfluorobutane, perfluoropentane and perfluorohexane. Perfluorocarbon compounds are a class of compounds with carbon-fluorine bonds, with high thermal stability, chemical inertness and low surface energy. The product prepared using this liquid perfluorocarbon as the core has a unique liquid-gas phase transition characteristic, can form microbubbles under ultrasonic stimulation, and the microbubbles further undergo inertial cavitation under the action of ultrasound to explode, thereby being able to release the drug molecules it carries at a fixed point in the target area, achieving the therapeutic effect of targeted delivery of drugs. In addition, the cavitation process of the microbubbles can also generate microflows and shear forces, stimulating the opening of the pores of the endothelial cell membrane and the channels between cells, and promoting the entry of therapeutic drugs into the cells.

[0089] In some embodiments, in the composite material, compared to 1L of fluorine phase liquid, the content of the biocompatible shell layer is 500g-1500g, such as 500g, 800g, 1000g, 1200g, 1400g or 1500g, and the content of the nanoparticles is 5g-80g, such as 5 g, 10 g, 20 g, 40 g, 60 g or 80 g.

[0090] It should be understood that the composite material may also contain other components that are beneficial to drug delivery, such as targeting peptides or cell-penetrating peptides.

[0091] The fifth aspect of the present invention provides a method for preparing the composite material according to the fourth aspect, the method comprising: (1) mixing fluorinated nanoparticles and fluorine phase liquid to obtain material A; (2) mixing the biocompatible material with the hydration liquid to obtain material B; (3) Mixing material A and material B and performing emulsification treatment to obtain the composite material.

[0092] In step (1), the fluorinated nanoparticles can be uniformly dispersed in the fluorine phase liquid by conventional means, such as one or more of a manual mixing method and an instrument vortex method.

[0093] In some embodiments, in step (1), the mixing conditions are: temperature of 0-99° C., and time of 1 min-99 min.

[0094] In some embodiments, the operating conditions of the manual mixing method or the instrument vortex method include: a rotation speed of 10-3000 rpm.

[0095] In step (1), there is no particular limitation on the amount of the fluorine phase liquid, as long as it can evenly disperse the fluorinated nanoparticles. In some embodiments, the amount of the fluorine phase liquid is such that the concentration of the fluorinated nanoparticles in material A is 5-80 mg / ml, preferably 10-50 mg / ml, and more preferably 20-40 mg / ml.

[0096] In some embodiments, in step (2), the hydration liquid comprises glycerol, propylene glycol and a solvent.

[0097] In some embodiments, in the hydration liquid, the volume ratio of glycerol, propylene glycol and solvent is 1:(0.5-3):(5-12).

[0098] There is no particularly strict restriction on the amount of hydration liquid used, as long as it can evenly disperse the biocompatible material of the present invention. In some embodiments, the concentration of the biocompatible material in material B is 0.5-8 mg / mL, preferably 1-5 mg / mL, and more preferably 2-4 mg / mL.

[0099] The solvent may be PBS buffer or DEPC water. For example, PBS buffer may be 1× PBS buffer (containing 130-140 mM NaCl, 2-3 mM KCl, 7-13 mM Na2HPO4, 1-3 mM KH2PO4), which can be commercially available.

[0100] In step (3), material A and material B are mixed by adding material A to material B and then emulsifying material A to evenly disperse it in material B. The purpose of the emulsification process is to change the reorganization mode of biocompatible materials such as liposomes or lipid membranes, thereby encapsulating the evenly dispersed material A to form droplets loaded with nanoparticles.

[0101] In some embodiments, based on 100 parts by volume of the material B, the amount of the material A is 1-40 parts by volume, preferably 2-15 parts by volume, and more preferably 3-8 parts by volume.

[0102] In some embodiments, in step (3), the emulsification treatment is performed by one or more of mechanical oscillation, ultrasonic cavitation and homogenization.

[0103] In some embodiments, in step (3), the emulsification treatment method includes ultrasonic cavitation.

[0104] In some embodiments, the emulsification treatment conditions include: a temperature of 0-5°C.

[0105] The mechanical oscillation method can be used to process perfluoropropane or perfluorobutane, for example, a uniformly mixed solution of A and B is placed in a sealed vial, the upper layer is filled with perfluorocarbon gas, and the vial is pressurized by continuously adding perfluorocarbon gas to liquefy the fluorocarbon gas. The pressure is generally controlled at 10-500 PSI, preferably 50-150 PSI; the oscillation frequency can be 2000-10000 rpm, preferably 3500-5500 rpm, and the oscillation time is 20-180 s, preferably 30-80 s. The droplet size can be regulated by adjusting the oscillation frequency and oscillation time.

[0106] Ultrasonic cavitation and homogenization methods can be applied to fluorine-phase liquids that are liquid at room temperature, such as perfluoropentane, perfluorohexane, perfluorooctane bromide, etc. For example, a uniformly mixed solution of A and B is placed in a container, and the container is placed in a constant temperature device to eliminate the effect of heat generated by the ultrasonic cavitation head or homogenization head on the solution temperature. The temperature is generally controlled at -5-25°C.

[0107] In some embodiments, the conditions of ultrasonic cavitation include: ultrasonic power of 60W-200W, ultrasonic time of 0.1min-10min, and duty cycle of 20%-60%.

[0108] In some embodiments, the homogenization conditions include: a homogenization speed of 3000-50000 rpm, and a homogenization time related to the volume of the solution, generally 1-120 min.

[0109] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0110] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0111] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0112] In the following examples, perfluorononanoic acid was the fluorinating agent, CAS: 375-95-1, purchased from SigmaAldrich; Perfluoroheptanoic acid was the fluorinating agent, CAS: 375-85-9, purchased from SigmaAldrich; Perfluorooctanoic acid was the fluorinating agent, CAS: 335-67-1, purchased from SigmaAldrich; The activation buffer contained 0.1 M morpholineethanesulfonic acid and 0.5 M NaCl; EDC was an activator, CAS: 25952-53-8, purchased from SigmaAldrich; Sulfo-NHS was the activating agent, CAS: 106627-54-7, purchased from SigmaAldrich; 1× PBS buffer contains 136mM NaCl, 2.67mM KCl, 10mM Na2HPO4, 2mM KH2PO4.

[0113] Concentrated PBS solution contains 1M sodium phosphate, 0.1M NaCl, pH 7.2-7.5 (Cat. No. 28372).

[0114] All drugs used were labeled with cy3 fluorescence.

[0115] The average particle size (number average particle size, unit: nm) and polydispersity coefficient of the nanodroplets were detected by a particle size analyzer (Malvern, Zatesizer pro) based on the DLS principle, and the data were approximated. Example

[0116] Example 1

[0117] (1) Preparation of fluorinated nanomaterials Dissolve perfluorononanoic acid in activation buffer at a concentration of 1 mg / ml; then add EDC at a final concentration of 0.25 mg / ml and allow to react for 10 min; add Sulfo-NHS to the above solution at a final concentration of 0.25 mg / ml; fully mix the solution and react at room temperature for 15 min; add excess 2-mercaptoethanol to quench EDC; use concentrated PBS solution to raise the pH of the reaction system to 7.0 to form solution ①.

[0118] G5-PAMAM was dissolved in DEPC water to a concentration of 1 mg / ml to form solution ②. An equal amount of solution ② was added to solution ①, mixed thoroughly, and reacted at room temperature for 2 hours; excess hydroxylamine hydrochloride was added to the final concentration to quench the reaction. NHS and EDC-NHS were removed by centrifugation using a 30KDa dialysis tube, and freeze-dried to form the fluorinated nanomaterial perfluorononanoic acid-(G5)-PAMAM.

[0119] Among them, in the fluorinated nanoparticles, the amine substitution rate is about 50%, the average particle size is about 88nm, and the polydispersity coefficient is about 0.02.

[0120] (2) Preparation of fluorinated drug-loaded nanoparticles The fluorinated nanomaterial and siRNA drug were dissolved in DEPC water, mixed and allowed to stand for 30 minutes to form a fluorinated drug-loaded nanoparticle solution, which was then freeze-dried to obtain a freeze-dried powder. The N / P ratio of the fluorinated nanomaterial and the siRNA drug was 10, and the weight ratio of the drug to the nanoparticle was about 0.1:1.

[0121] (3) Preparation of nanodroplets encapsulating fluorinated drug-loaded nanoparticles The lyophilized powder was added into perfluorohexane and mixed by blowing in an ice-water bath to make the fluorinated drug-loaded nanoparticles evenly dispersed in the fluorine phase solution to obtain material A.

[0122] DSPC, DSPE, CHO, and PEG40s were weighed and mixed in a weight ratio of 100:35:25:25 and dissolved in ethanol. After removing the ethanol by a rotary evaporator, they were dissolved in a hydrating solution (mixed with glycerol, propylene glycol and 1× PBS buffer in a volume ratio of 1:1.5:8.5) to form a liposome solution, recorded as material B, in which the final concentration of DSPC was 4 mg / ml.

[0123] Take 500 μL of material A and add it to 10 mL of material. Use ultrasonic cavitation in an ice water bath to dissolve A and evenly disperse it in solution B. The power of ultrasonic cavitation is 100 W, the ultrasonic time is 5 min, and the duty cycle is 45%. After ultrasound, centrifuge the lower layer of liquid at a speed of 4000 rpm for 10 min, and then suck off the upper layer of solution again to remove the unstructured membrane material, forming droplets encapsulating drug-loaded nanoparticles, which are counted as I1.

[0124] The average particle size and polydispersity coefficient of the droplets are shown in Table 1.

[0125] Example 2

[0126] (1) Preparation of fluorinated nanomaterials The fluorinated nanomaterial was prepared according to the method described in step (1) of Example 1, except that (1) perfluoroheptanoic acid was used instead of perfluorononanoic acid; and (2) the method for preparing solution ② was different, specifically, DLin-MC3-DMA was dissolved in DEPC water to a concentration of 7.5 mg / ml to form solution ②, and finally the intermediate perfluoroheptanoic acid-DLin-MC3-DMA was formed.

[0127] Using pure ethanol as solvent, 150 mg / mL intermediate solution, 10 mg / mL DSPC solution, 10 mg / mL cholesterol solution, and 10 mg / mL mPEG2000-DMG solution were prepared respectively, and the above solutions were mixed to prepare a perfluoroheptanoic acid-DLin-MC3-DMA LNP mixture solution. Among them, the volume ratio of fluorinated nanomaterial solution: DSPC solution: cholesterol solution: mPEG2000-DMG solution is 1:2:4:1.

[0128] Among them, in the fluorinated nanoparticles, the amino substitution rate is about 55%, the average particle size is about 76nm, and the polydispersity coefficient is about 0.02.

[0129] (2) Preparation of fluorinated drug-loaded nanoparticles A 2.0 mg / mL siRNA buffer was prepared using a citrate buffer, and then the perfluoroheptanoic acid-DLin-MC3-DMA LNP mixture solution was quickly mixed with the siRNA buffer, incubated at room temperature, and dialyzed to remove ethanol and buffer. After dialysis, freeze-dried to obtain drug-loaded nanoparticle freeze-dried powder.

[0130] (3) Preparation of nanodroplets encapsulating fluorinated drug-loaded nanoparticles The lyophilized powder was added into perfluoropentane and mixed by blowing in an ice-water bath to make the fluorinated drug-loaded nanoparticles evenly dispersed in the fluorine phase solution to obtain material A.

[0131] DSPC, DSPE, CHO, and PEG40s were weighed and mixed in a weight ratio of 100:35:25:25 and dissolved in ethanol. After removing the ethanol by a rotary evaporator, they were dissolved in a hydrating solution (mixed with glycerol, propylene glycol and 1× PBS buffer in a volume ratio of 1:1.5:8.5) to form a liposome solution, recorded as material B, in which the final concentration of DSPC was 4 mg / ml.

[0132] Take 500 μL of material A and add it to 10 mL of material. Use ultrasonic cavitation in an ice water bath to dissolve A and evenly disperse it in solution B. The power of ultrasonic cavitation is 120 W, the ultrasonic time is 4 min, and the duty cycle is 50%. After ultrasound, the lower layer of liquid is centrifuged at a speed of 4000 rpm for 10 min, and the upper layer of solution is sucked off again to remove the unstructured membrane material, forming droplets encapsulating drug-loaded nanoparticles, which are counted as I2.

[0133] The average particle size and polydispersity coefficient of the droplets are shown in Table 1.

[0134] Example 3

[0135] (1) Preparation of fluorinated nanomaterials The fluorinated nanomaterial was prepared according to the method described in step (1) of Example 1, except that (1) perfluorooctanoic acid was used instead of perfluorononanoic acid; and (2) the method for preparing solution ② was different, specifically, ALC-0315 was dissolved in DEPC water to a concentration of 10 mg / ml to form solution ②, and finally the intermediate perfluorooctanoic acid-ALC-0315 was formed.

[0136] Using pure ethanol as solvent, 150 mg / mL intermediate solution, 10 mg / mL DPPC solution, 10 mg / mL cholesterol solution, and 10 mg / mL ALC-0159 solution were prepared respectively, and the above solutions were mixed to prepare a perfluorooctanoic acid-ALC-0315 LNP mixture solution. Among them, the volume ratio of intermediate solution: DPPC solution: cholesterol solution: ALC-0159 solution is 1:3:5:1.2.

[0137] Among them, in the fluorinated nanoparticles, the amino substitution rate is about 45%, the average particle size is about 110nm, and the polydispersity coefficient is about 0.03.

[0138] (2) Preparation of fluorinated drug-loaded nanoparticles The thin film emulsification method was adopted to dissolve the mixture solution and paclitaxel in anhydrous ethanol, and the mixture was placed in a round-bottom flask for rotary evaporation to remove the solvent. A hydration solution was then added for hydration to finally form a fluorinated drug-loaded nanoparticle solution with a final paclitaxel concentration of 2 mg / ml.

[0139] (3) Preparation of nanodroplets encapsulating fluorinated drug-loaded nanoparticles The fluorinated drug-loaded nanoparticle solution was added to perfluorohexane, and the mixture was mixed by blowing in an ice-water bath to make the fluorinated drug-loaded nanoparticles evenly dispersed in the fluorine phase solution to obtain material A.

[0140] DSPC, DSPE, CHO, and PEG40s were weighed and mixed in a weight ratio of 100:35:25:25 and dissolved in ethanol. After removing the ethanol by a rotary evaporator, they were dissolved in a hydrating solution (mixed with glycerol, propylene glycol and 1× PBS buffer in a volume ratio of 1:1.5:8.5) to form a liposome solution, recorded as material B, in which the final concentration of DSPC was 4 mg / ml.

[0141] Take 500 μL of material A and add it to 10 mL of material. Use ultrasonic cavitation in an ice water bath to dissolve A and evenly disperse it in solution B. The power of ultrasonic cavitation is 80 W, the ultrasonic time is 7 min, and the duty cycle is 40%. After ultrasound, the lower layer of liquid is centrifuged at a speed of 4000 rpm for 10 min, and the upper layer of solution is sucked off again to remove the unstructured membrane material, forming droplets encapsulating drug-loaded nanoparticles, which are counted as I3.

[0142] The average particle size and polydispersity coefficient of the droplets are shown in Table 1.

[0143] Example 4 Example 4a: The method described in Example 1 is followed, except that in the fluorinated nanoparticles, the amino substitution rate is 60%, the average particle size is about 64 nm, and the polydispersity coefficient is about 0.03, to prepare droplets I4a.

[0144] Example 4b: The method described in Example 1 is followed, except that in the fluorinated nanoparticles, the amino substitution rate is 40%, the average particle size is about 150 nm, and the polydispersity coefficient is about 0.03, to prepare droplets I4b.

[0145] The average particle size and polydispersity coefficient of the droplets are shown in Table 1.

[0146] Example 5 Example 5a: The method described in Example 1 was followed, except that 3-fluorobenzoic acid was used instead of perfluorononanoic acid to prepare droplet I5a.

[0147] Example 5b: The method described in Example 1 was followed, except that perfluorobutyric anhydride was used instead of perfluorononanoic acid to prepare droplet I5b.

[0148] The average particle size and polydispersity coefficient of the droplets are shown in Table 1.

[0149] Example 6 Example 6a: The operation was carried out in accordance with the method described in Example 1, except that the ultrasonic parameters during ultrasonic cavitation were: 195 W, 15 min, and a duty cycle of 60%; droplets I8a were prepared.

[0150] Example 6b: The operation was carried out in accordance with the method described in Example 1, except that the ultrasonic parameters during ultrasonic cavitation were: 65 W, 20 min, and a duty cycle of 25%; droplets I8b were prepared.

[0151] The average particle size and polydispersity coefficient of the droplets are shown in Table 1.

[0152] Comparative Example 1 The method of Example 1 was followed, except that the polymer nanoparticles used were not coupled with fluorinated groups, and finally droplets were obtained, which were recorded as D1.

[0153] The average particle size and polydispersity coefficient of the droplets are shown in Table 1.

[0154] Comparative Example 2 The method of Example 2 was followed, except that the lipid nanoparticles used were not coupled with fluorinated groups, and droplets were finally obtained, which were recorded as D2.

[0155] The average particle size and polydispersity coefficient of the droplets are shown in Table 1.

[0156] Comparative Example 3 The method of Example 3 was followed, except that the lipid nanoparticles used were not coupled with fluorinated groups, and droplets were finally obtained, which were recorded as D3.

[0157] The average particle size and polydispersity coefficient of the droplets are shown in Table 1.

[0158] Comparative Example 4 Comparative Example 4a: The method described in Example 1 was followed, except that in the fluorinated nanoparticles, the amino substitution rate was 20%, the average particle size was about 20 nm, and the polydispersity coefficient was about 0.04, to prepare droplets D4a.

[0159] Comparative Example 4b: The method described in Example 1 was followed, except that in the fluorinated nanoparticles, the amino substitution rate was 70%, the average particle size was about 10 nm, and the polydispersity coefficient was about 0.05, to prepare droplets D4b.

[0160] The average particle size and polydispersity coefficient of the droplets are shown in Table 1.

[0161] Test Case (1) Droplet stability The stability of the droplets in the body is reflected by the half-life of the droplets. The longer the half-life, the higher the stability. The specific test method is: C57BL / 6 mice are used as experimental subjects, and the drug-loaded droplets are injected through the tail vein of the mice. The concentration of the drug-loaded droplets is adjusted to 1×10 11 / ml, the injection dose was 0.1ml / kg, blood was drawn from mice at different times, and the phospholipid content in the blood was monitored by HPLC, and the time corresponding to the time when the phospholipid concentration in the blood was half of the initial injection concentration was set as the half-life of the droplet.

[0162] The half-life results of the droplets of the embodiment and the comparative example are respectively recorded in Table 1.

[0163] (2) Determination of drug loading in droplets The drug content in the droplets was detected by liquid chromatography-mass spectrometry (LC-MS). The specific test method is as follows: After obtaining the absorption peak and concentration curve of the standard drug using LC-MS, the droplets were dissolved in pure acetonitrile to obtain a clear and transparent solution of the drug, the solution was diluted to an appropriate multiple, and the sample was tested to obtain the drug concentration, and finally the specific drug content in the droplets was calculated. The drug loading was calculated using the following formula: Drug-loading capacity = [drug content in nanodroplets / (drug content in nanodroplets + membrane material)] * 100% The drug loading results of the droplets of the embodiment and the comparative example are respectively recorded in Table 1.

[0164] (3) Determination of brain drug delivery efficiency under ultrasound activation The droplets of I1-I3 and D1-D3 were taken to measure the brain drug delivery efficiency under ultrasound activation, and the specific operations were as follows.

[0165] Eight-week-old BALB / c nude female mice were used as experimental subjects. After inhalation of isoflurane anesthesia and fixation on a brain positioning device, a craniotomy was performed and 0.5 cm × 0.5 cm of the skull was removed. Droplets were injected through the tail vein at a concentration of 1 × 10 11 / ml, the injection dose was 0.1ml / kg. The Vearsonics ultrasound imaging system was used for observation in the treatment mode. The L22-8 ultrasound probe (center frequency 15MHz) was used to select the right hemisphere (1mm X 1mm) as the ultrasound administration area, and the activation parameters were set as follows: voltage 35V, wave number 6, and ultrasound time 10min. 10 minutes after ultrasound treatment, 4% PFA was used for cardiac perfusion, and the brain was removed and fixed with 4% paraformaldehyde at 4°C overnight, and then fixed with 30% sucrose solution (4°C) until it sank to the bottom of the container. The brain tissue was placed in an OCT mixture and quickly frozen to -80 °C. Subsequently, 30 μm sections were cut using a cryostat (Leica 3050scryostat). Brain fluorescence imaging was then performed, and Cy3 fluorescence was captured with an excitation wavelength of 550 nm and an absorption wavelength of 570 nm. ImageJ software was used to quantitatively analyze the Cy3 fluorescence value of the fluorescent images of the immunofluorescence images, and the left brain of the mouse with the same size (1mm X 1mm) and symmetrical position as the right brain was selected as the non-ultrasound control group.

[0166] Brain drug delivery efficiency improvement factor = ((Cy3 fluorescence value of ultrasonically treated area - Cy3 fluorescence value of non-ultrasonicated area) / Cy3 fluorescence value of non-ultrasonicated area) × 100% The results of the brain drug delivery enhancement factor measured by the droplets of the examples and comparative examples are respectively recorded in Table 1.

[0167] Figure 1 The red color in the figure is the siRNA drug labeled with Cy3 fluorescence, indicating that the drug-loaded nanoparticles are successfully encapsulated in the droplets. Figure 2Figure a shows the droplets before ultrasound action, where they have not exploded; Figure b shows the droplets after ultrasound action, where the ultrasound image shows that the droplets have significantly exploded, indicating that the prepared droplets can undergo ultrasonic cavitation under ultrasound action and further explode, thereby releasing the drug.

[0168] Table 1 serial number Average particle size / nm Polydispersity coefficient Half-life / h Drug loading rate / % Increased fold of drug delivery efficiency in the brain***P < 0.0001, t-test I1 750 0.1 8 90 20 I2 800 0.1 7.5 88 18 I3 650 0.2 7 85 15 I4a 980 0.3 7 81 10 I4b 990 0.3 6.5 83 11 I5a 550 0.3 6.5 80 12 I5B 560 0.3 6 83 11 I6a 600 0.3 6.5 75 7 I6b 520 0.3 6 78 8 D1 400 0.8 2 4 0.2 D2 380 0.9 1.5 6 0.1 D3 200 0.7 1 5 0.1 D4a 1200 0.6 2 11 0.3 D4b 1300 0.8 3 10 0.6 Note: In Table 1, the average particle size and polydispersity coefficient are approximate numbers.

[0169] It can be seen from Table 1 that compared with the prior art, the drug delivery system prepared by the present invention has higher blood stability and higher drug loading capacity, can burst at the target site and under the activation of the ultrasonic imaging probe, release drugs at high concentration, and significantly improve the drug delivery amount at the target site.

[0170] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0171] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A fluorinated nanoparticle, characterized in that: The fluorinated nanoparticles include nanoparticles and fluorinated groups connected to the nanoparticles through amide bonds and located on the outer layer of the nanoparticles; In the fluorinated nanoparticles, the amino substitution rate is 35%-65%.

2. The fluorinated nanoparticles according to claim 1, characterized in that The fluorinated group comprises one or more of the groups shown in Formula I and Formula II; Formula I; Formula II; Wherein, in Formula I, x is an integer of 0-3, y is an integer of 0-20, and z is an integer of 0-8; when y is 0, R1 is CF3, CHF2 or CH2F, and when y is not 0, R1 is CH3, CF3, CHF2 or CH2F; In formula II, R2 to R6 are each independently H, CH3, OH, NO2O, CF3, F, CH2OH, CN, NCO or (CF2) a CF3, and at least one of R2 to R6 is a F-containing group; a is an integer of 1-20; Preferably, in Formula I, x is an integer of 0-1, y is an integer of 0-15, and z is an integer of 0-2; more preferably, the group represented by Formula I is selected from one or more of C1-C15 perfluoroalkyl groups and their derivatives; Preferably, R2 to R6 are each independently H, F, CF3 or (CF2) a CF3; a is an integer of 1-10; more preferably, the group represented by formula II is selected from one or more of 3-fluorobenzyl, 3,5-difluorobenzyl, 2,3,5,6-tetrafluoro-4-methylbenzyl, pentafluorobenzyl, 2-fluoro-3-(trifluoromethyl)benzyl and derivatives thereof.

3. The fluorinated nanoparticles according to claim 1 or 2, characterized in that The average particle size Dv of the fluorinated nanoparticles 50 10 nm -800 nm, preferably 50 nm -500 nm; The polydispersity coefficient of the fluorinated nanoparticles is 0.02-0.03; The nanoparticles are lipid nanoparticles or polymer nanoparticles; Preferably, the lipid nanoparticles contain ionizable cationic lipids, cholesterol, auxiliary phospholipids and PEGylated lipids; preferably, in the lipid nanoparticles, the molar ratio of ionizable cationic lipids, cholesterol, auxiliary phospholipids and polyethylene glycol is (20-60): (30-50): (5-60): (1-30); Preferably, the polymer nanoparticles are selected from one or more of linear polymers, dendritic macromolecular polymers and hyperbranched polymers; More preferably, the raw material of the polymer nanoparticles is a polymer modified with a primary amino group, and the polymer is selected from one or more of polysaccharides and their derivatives, aliphatic polyester polymers, polyglutamic acid, polyethylene glycol, polystyrene and polyamide; Preferably, the fluorinated nanoparticles contain a drug; More preferably, in the fluorinated nanoparticles, the weight ratio of the drug to the nanoparticles is 0.05-50:1; More preferably, the drug is a chemotherapeutic drug and / or a nucleic acid drug.

4. A method for preparing the fluorinated nanoparticles according to any one of claims 1 to 3, characterized in that: The method comprises: under reaction conditions, by chemical coupling method, coupling the fluorination agent with the nanoparticles through amide bonds to obtain fluorinated nanoparticles; Preferably, the chemical coupling method is a carboxyl-amino reaction coupling method; More preferably, the chemical coupling method comprises: (a) adding a fluorinating agent, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysulfosuccinimide to an activation buffer in sequence, and then reacting for 5 min to 30 min; (b) adding a first quenching agent to the reaction product of step (a) to quench the reaction, and then adjusting the pH of the reaction system to 7-9 to obtain solution ①; (c) mixing the nanoparticles with water and adjusting the pH to 7-9 to obtain solution ②; (d) adding solution ② to solution ①, mixing and reacting for 0.5 h to 24 h, and then adding a second quencher to quench the reaction; (e) purifying the product obtained in step (d) to obtain a fluorinated nanomaterial; Preferably, the activation buffer comprises morpholineethanesulfonic acid and NaCl, and in the activation buffer, the molar ratio of morpholineethanesulfonic acid to NaCl is (1-20): (1-30); Preferably, the molar ratio of the fluorinating agent, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysulfosuccinimide is (1-40):(2-50):(2-50); Preferably, the fluorinating agent comprises one or more of the fluorinated groups shown in Formula I and Formula II, more preferably one or more of carboxylic acid compounds and their derivatives and acid anhydride compounds and their derivatives.

5. Use of the fluorinated nanoparticles according to any one of claims 1 to 3 in the preparation of a hydrophilic and fluorine-free carrier.

6. A composite material, characterized in that: The composite material comprises a biocompatible shell layer and a fluorine phase liquid encapsulated in the shell layer, wherein the fluorinated nanoparticles according to any one of claims 1 to 3 are dispersed in the fluorine phase liquid; Preferably, the particle size of the composite material is 5-50 times the particle size of the fluorinated nanoparticles; Preferably, the average particle size Dv of the composite material is 50 500nm-1000nm; Preferably, the polydispersity coefficient of the composite material is 0.1-0.

3.

7. The composite material according to claim 6, characterized in that The biocompatible shell comprises a lipid, preferably a phospholipid; and / or The fluorine phase liquid is an organic fluorine in a phase-changeable liquid state, preferably a perfluorocarbon, more preferably a perfluorocarbon selected from C3 or above; Preferably, the composite material further comprises an emulsifier and optionally cholesterol; More preferably, the emulsifier is selected from one or more of polyethylene glycol 4000, polyethylene glycol 40s, polyoxypropylene polyoxyethylene block polyether, polyethylene glycol 1400 and polysorbate 80; Preferably, in the composite material, compared to 1L of fluorine phase liquid, the content of the biocompatible shell layer is 500g-1500g, and the content of the nanoparticles is 5g-80g; Preferably, the content of the emulsifier is 10-80 parts by weight, more preferably 10-60 parts by weight, relative to 100 parts by weight of the lipid, and the content of cholesterol is 60 parts by weight or less, more preferably 10-60 parts by weight.

8. A method for preparing the composite material according to claim 6 or 7, characterized in that: The method includes: (1) mixing fluorinated nanoparticles and fluorine phase liquid to obtain material A; (2) mixing the biocompatible material with the hydration liquid to obtain material B; (3) mixing material A and material B and performing emulsification treatment to obtain the composite material; Preferably, the emulsification treatment is carried out by one or more of mechanical oscillation, ultrasonic cavitation and homogenization, more preferably ultrasonic cavitation; More preferably, the conditions of ultrasonic cavitation include: ultrasonic power of 60W-200W, ultrasonic time of 0.1min-10min, duty cycle of 20%-60%; Further preferably, the conditions of ultrasonic cavitation include: ultrasonic power of 70W-140W, ultrasonic time of 3min-8min, and duty cycle of 35%-55%.

9. The method according to claim 8, characterized in that The hydrating fluid comprises glycerin, propylene glycol and a solvent; Preferably, in the hydration liquid, the volume ratio of glycerol, propylene glycol and solvent is 1:(0.5-3):(5-12); Based on 100 parts by volume of the material B, the amount of the material A is 1-40 parts by volume, preferably 2-15 parts by volume, and more preferably 3-8 parts by volume.

10. Use of the fluorinated nanoparticles according to any one of claims 1 to 3 or the composite material according to claim 6 or 7 in drug delivery.